2021
DOI: 10.1177/23949643211042246
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Value Preferences in Healthcare: Insights for Value-centred Management

Abstract: Advances in healthcare service research emphasize a value-driven approach in healthcare by pressing the need to acknowledge what matters to the patient against the conventional approach of what should be provisioned in the service. This research study adopts a consumer-centric perspective of value creation, and explores consumer value preferences in healthcare services, using netnography of online consumer reviews of cancer patients. Six different types of consumer value are identified, which carry varying con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Of the total number of articles, 26.4% ( n = 14) reported that their study had been reviewed by an ethics board (Alang & Fomotar, 2015; Andréasson et al, 2018; Aragão et al, 2018; Boursier et al, 2022; Cano-Hila & Argemí-Baldich, 2021; Ellinghaus et al, 2021; Gün & Şenol, 2019; Kendal et al, 2017; Lawless et al, 2020, 2022; Moura & Aschemann-Witzel, 2021; Schuman et al, 2019; Vale et al, 2019; Wallace et al, 2018), while 56.6% ( n = 30) reported that their study had not been reviewed (Ari & Mari, 2021; Baptista et al, 2021; Bayen et al, 2021; Bîră et al, 2020; Björkman & Salzmann-Erikson, 2018; Botelle & Willott, 2020; Cuomo et al, 2020; Eriksson et al, 2014; Eriksson & Salzmann-Erikson, 2013, 2016b, 2018; Gatrell, 2019; Holmgren et al, 2018; Johansson & Andreasson, 2017; Keeling et al, 2015; Liang & Scammon, 2011; Manning Hutson et al, 2022; Nemec et al, 2018; Nimrod, 2011; Numer et al, 2022; Poppi, 2021; Salzmann-Erikson, 2016, 2017; Salzmann-Erikson & Eriksson, 2011; Saxena et al, 2021; Song, 2020; Strand, 2022, p. 202; Strand & Gustafsson, 2020; Thunborg & Salzmann-Erikson, 2017; Van Hout & Hearne, 2014); four articles reported that they had applied to an ethics review board (ERB) but had been deemed exempt because their work was not considered human subjects research (De Gagne et al, 2021; Giles et al, 2015; …”
Section: Resultsmentioning
confidence: 99%
“…Of the total number of articles, 26.4% ( n = 14) reported that their study had been reviewed by an ethics board (Alang & Fomotar, 2015; Andréasson et al, 2018; Aragão et al, 2018; Boursier et al, 2022; Cano-Hila & Argemí-Baldich, 2021; Ellinghaus et al, 2021; Gün & Şenol, 2019; Kendal et al, 2017; Lawless et al, 2020, 2022; Moura & Aschemann-Witzel, 2021; Schuman et al, 2019; Vale et al, 2019; Wallace et al, 2018), while 56.6% ( n = 30) reported that their study had not been reviewed (Ari & Mari, 2021; Baptista et al, 2021; Bayen et al, 2021; Bîră et al, 2020; Björkman & Salzmann-Erikson, 2018; Botelle & Willott, 2020; Cuomo et al, 2020; Eriksson et al, 2014; Eriksson & Salzmann-Erikson, 2013, 2016b, 2018; Gatrell, 2019; Holmgren et al, 2018; Johansson & Andreasson, 2017; Keeling et al, 2015; Liang & Scammon, 2011; Manning Hutson et al, 2022; Nemec et al, 2018; Nimrod, 2011; Numer et al, 2022; Poppi, 2021; Salzmann-Erikson, 2016, 2017; Salzmann-Erikson & Eriksson, 2011; Saxena et al, 2021; Song, 2020; Strand, 2022, p. 202; Strand & Gustafsson, 2020; Thunborg & Salzmann-Erikson, 2017; Van Hout & Hearne, 2014); four articles reported that they had applied to an ethics review board (ERB) but had been deemed exempt because their work was not considered human subjects research (De Gagne et al, 2021; Giles et al, 2015; …”
Section: Resultsmentioning
confidence: 99%
“…Social capital can be created and strengthened by spiritual capital, particularly when it comes to fostering normative conduct that fosters collaborative networks for long-term economic sustainability. Jauhari and Sanjeev (2010) and Saxena et al (2021) have confirmed in the context of business continuity, spiritual capital and social management processes can help to foster the positive relationships required to expand the business scale. Unfortunately, because the idea of spiritual capital and the social management process is rarely articulated, there is little study on the connection between socially friendly business strategy and social sustainability performance.…”
Section: Introductionmentioning
confidence: 92%
“…The phrase “social management process” refers to the business’s strategic initiatives to implement the management process to achieve the three sustainability pillars, particularly on the social front. Additionally, businesses with substantial social capital and social management practices demonstrate a solid commitment to being socially responsible and positively impacting both sustainable development and community welfare (Saxena et al , 2021).…”
Section: Introductionmentioning
confidence: 99%